A STUDY OF LIPID CHANGES IN RHEUMATOID ARTHRITIS PATIENTS - MANJULA DEVI.A.J,; SUMATHI.K.,; SHANTHI.B., (International Journal of Pharma and Bio Sciences, 2013)
Lipoprotein abnormalities are usually observed in chronic inflammatory conditions like rheumatoid arthritis. The aim of the study is to determine the lipoprotein abnormalities in patients with rheumatoid arthritis. 52 patients of rheumatoid arthritis of varying age groups are choosen for this study and 37 healthy people were taken for the control. The estimation of triglycerides done by method adopted in Foster and Dunn. The estimation of serum cholesterol was carried out by using modified Zak’s method. The estimation of serum high density lipoproteins was done by phosphotungstate/ magnesium method. The marked reduction of cholesterol, HDL, LDL, VLDL were noticed in rheumatoid arthritis patients with significant p-values compared to normal values in control groups. The study concluded that hypolipoproteinemia in rheumatoid arthritis may be due to anemia. The hypolipidimiae may be caused by general debilitating illness found in rheumatoid arthritis causing cachexia, which in turn may cause hypoproteinimiae.